PROGRAM INTERVENSI PENCEGAHAN PENINGKATAN KASUS HIPERTENSI DI WILAYAH KERJA PUSKESMAS SINDANG JAYA - Laurensia Laurensia; Edwin Destra; Hayuningrat Odyssey Saint; Muhammad Abdu Quraisy Syihab; Ernawati Ernawati (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Introduction: Hypertension in Southeast Asia had 39.9% of incidence rate in 2020. In Indonesia, there was an increase in hypertension from 2013 to 2018. In Tangerang Regency in 2018 the number of people with hypertension was recorded as much as 274,792 residents. Objective: To reduce the incidence of hypertension in the working area of ​​the Sindang Jaya Health Center. Methods: The study used an assessment with pre-test and post-test. The intervention was carried out in the form of counseling to increase public knowledge in the Sindang Jaya Health Center Work Area. The sample in this study was selected by non-random consecutive sampling. The independent variable in this study is the intervention carried out to increase public knowledge. The dependent variable in this study is the change in knowledge of the intervention carried out. Results: 40 counseling participants experienced an increase in knowledge after the intervention in 14 selected aspects as an indication of knowledge. Conclusion: The intervention in the form of counseling succeeded in increasing public knowledge about hypertension. It is hoped that there will be changes in people's attitudes and behavior in preventing the increase in new cases of hypertension in the community.